2006
DOI: 10.1192/bjp.188.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Mental health, burnout and job satisfaction among mental health social workers in England and Wales

Abstract: Stress may exacerbate recruitment and retention problems. Employers must recognise the demands placed upon MHSWs and value their contribution to mental health services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
144
4
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 12 publications
13
144
4
11
Order By: Relevance
“…These results corroborate Brazilian studies (De Marco et al, 2008;Ishara et al, 2014;Rebouças et al, 2007) and contradict those of international studies reporting high levels of dissatisfaction (Evans et al, 2006;Hannigan et al, 2000). The highest mean score concerned the relationship established with coworkers, while the mean scores concerning the service's infrastructure and working conditions were the lowest.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…These results corroborate Brazilian studies (De Marco et al, 2008;Ishara et al, 2014;Rebouças et al, 2007) and contradict those of international studies reporting high levels of dissatisfaction (Evans et al, 2006;Hannigan et al, 2000). The highest mean score concerned the relationship established with coworkers, while the mean scores concerning the service's infrastructure and working conditions were the lowest.…”
Section: Discussioncontrasting
confidence: 43%
“…Various studies have assessed mental health services using satisfaction measures and most focused on patient satisfaction (Blenkiron & Hammill, 2003;Gani et al, 2011;Heckert, Teixeira, & Trindade, 2006;Holikatti et al, 2012;Kantorski et al, 2009;Silva, Bandeira, Scalon, & Quáglia, 2012), followed by that of healthcare providers (De Marco, Cítero, Moraes, & Nogueira-Martins, 2008;Evans et al, 2006;Hannigan, Edwards, Coyle, Fothergill, & Burnard, 2000;Ishara et al, 2014;Pelisoli, Moreira, & Kristensen, 2007;Rebouças et al, 2007). The satisfaction of families was the least studied (Bandeira et al, 2011;Perreault et al, 2011;Santos & Cardoso, 2014;Stengard, Honkonen, Koivisto, & Salokangas, 2000).…”
mentioning
confidence: 99%
“…Gli studi sui determinanti del burnout nei servizi di salute mentale hanno in genere appuntato la propria attenzione su fattori individuali di tipo socio-demografico (Fagin et al, 1996;Edwards et al, 2000), su caratteristiche individuali di tipo lavorativo (Prosser et al, 1999;Kilfedder et al, 2001;Evans et al, 2006) o su tratti personologici predisponenti (Naisberg-Fennig et al, 1991;Deary et al, 1996a). Tuttavia, studi più recenti hanno ampliato la cornice teorica del concetto di burnout dal singolo lavoratore alla struttura organizzativa per la quale il singolo lavora.…”
unclassified
“…Studies that explored determinants of burnout in mental health settings generally focused on individual socio-demographic factors (Fagin et al, 1996;Edwards et al, 2000), individual occupational characteristics (Prosser et al, 1999;Kilfedder et al, 2001;Evans et al, 2006) and predisposing personality traits (Naisberg-Fennig et al, 1991;Deary et al, 1996a). Yet, recent research has expanded the theoretical burnout framework to include perceived organisational sources of stress.…”
mentioning
confidence: 99%
“…However the international evidence suggests that the JDC hypothesis is not universally supported across all occupations, nor across all geographical boundaries (van der Doef and Maes, 1999). One study of mental health social workers in England has found that high job demands and low control were individually associated with low wellbeing, but did not test for interaction effects (Evans et al, 2006). …”
Section: Conceptual Framework: the Job Demand / Control Modelmentioning
confidence: 99%